Sobre a agricultura irrigada no semiárido: Uma análise histórica e atual de diferentes opç\~oes de política - César Nunes de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– In the last decades, in an attempt to promote a model of agriculture of high productivity in the semiarid, successive governments have invested in the water infrastructure for the creation of several irrigation districts in the region. The purpose of this work is to analyze historically the evolution of irrigated agriculture and the policy options of the Federal Government in relation to its development in the Brazilian semiarid. From this portrait, the objective is to discuss the potential of irrigated agriculture as an inducer of agricultural development in the region and about different policy options for irrigation in the semiarid region. The success of these ventures in relation to the income and jobs generated, number of farmers settled, companies installed, among other factors, is diverse. There are those perimeters installed at the Petrolina and Juazeiro poles, which have developed over the decades until they reached the current stage, in which a modern and profitable agricultural production is turned to export. Otherwise, there are those that have not been completed and are partially operative.
Keywords: Q1; Q18; 330; semiarid; irrigated agriculture; national irrigation policy